Carrying Out Energy Audits to Determine Measures to Save Energy Resources - Vasilenko, O.; Shkrehal, O.; Kletska, O.; Onyshchenko, A.; Voznenko, S. (International Journal of Engineering and Technology, 2018)
It is important for a modern consumer of thermal energy to know and be able to reduce the consumption of thermal energy, for which purpose an energy audit should be conducted. Today, three types of energy audit of residential buildings are used in Ukraine. The first one is development of the energy performance certificate of the building. The obtained energy performance certificate will give an idea of the level of thermal losses of the building and identify the main areas where measures to reduce the consumption of energy resources should be taken. The second method involves carrying out experimental studies to determine the class of air permeability of enclosing structures, which also makes it possible to assess the level of heat losses of the building and the condition of the ventilation system of the building. The third type of energy audit involves carrying out thermal imaging of the building envelope for the subsequent analysis of infrared images. A methodological approach has been developed for processing multiple infrared images. An energy inspection of a residential house has been conducted on the basis of which an energy performance certificate was compiled. The premises of the residential building have been tested for air permeability. Considering the main types of energy audit, its advantages and disadvantages have been determined both for the consumer and for the employees who conduct the audit.Â Â
Keywords: air permeability; energy audit; energy performance certificate of the building; infrared images